Differentiate the roles of CA channel subtypes in insulin secretion - Chen, Peng. (2010)
Calcium ion entry through VSCCs is a key step in the coupling of β-cell depolarization with insulin secretion. VSCCs have been described in cell preparations obtained from various species and their biophysical and pharmacological properties have been characterized. Most cells have been shown to express mainly high voltage activated (HVA) VSCCs although low voltage activating (LVA) VSCCs have also been observed in some cases. Ca2+ influx into beta cells was completely prevented by removal of extracellular Ca2+, but was still remained by the DHP-Ca2+ channel blocker. Beta cell was known to have L-type and non-L-type VSCCs. In human beta cells both DHPs-sensitive and insensitive HVA VSCCs are present. Previous studies reported that RINm5F cells have DHPs or ω-conotoxin GVIA-sensitive channel as well and both DHPs and ω-conotoxin GVIA-insensitive components. RINm5F cells possess at least three HVA channels; an L-type channels, an N-type and more non L- or non N-type channels. However, the correlation between insulin release and Ca2+ channel subtypes controlling insulin release has not been intensively examined in RINm5F cells. In the present study, we have investigated the calcium channel subtypes responsible for insulin secretion and exocytosis by radioimmunoassay (RIA) and amperometric measurement using calcium channel antagonists, nifedipine, ω-conotoxin GVIA, ω-agatoxin IVA (although this toxin does block Q-channels at high concentration, we used low concentration to have selectivity), and ω-conotoxin MVIIC, which are known as blockers of L, N, P and Q-type calcium channels, respectively.